Suicide awareness and prevention - Hazelden Foundation (Center Cit, MN : Hazelden Foundation, 2003)
This program explores the reality of suicide among teens and presents solutions. Teens will also learn how suicide affects parents, other family members, and classmate. The facilitator's guide helps to get teens thinking and talking about suicide awareness and prevention
Title from title screen
Exective producer, David Roth
Keywords: Suicidal behavior -- United States; Suicide -- United States -- Prevention